Epigenetic regulation of adaptive responses of forest tree species to the environment. Issue 2 (17th January 2013) - Bräutigam, Katharina; Vining, Kelly J.; Lafon‐Placette, Clément; Fossdal, Carl G.; Mirouze, Marie; Marcos, José Gutiérrez; Fluch, Silvia; Fraga, Mario Fernández; Guevara, M. Ángeles; Abarca, Dolores; Johnsen, Øystein; Maury, Stéphane; et al.
Abstract Epigenetic variation is likely to contribute to the phenotypic plasticity and adaptative capacity of plant species, and may be especially important for long‐lived organisms with complex life cycles, including forest trees. Diverse environmental stresses and hybridization/polyploidization events can create reversible heritable epigenetic marks that can be transmitted to subsequent generations as a form of molecular "memory". Epigenetic changes might also contribute to the ability of plants to colonize or persist in variable environments. In this review, we provide an overview of recent data on epigenetic mechanisms involved in developmental processes and responses to environmental cues in plant, with a focus on forest tree species. We consider the possible role of forest tree epigenetics as a new source of adaptive traits in plant breeding, biotechnology, and ecosystem conservation under rapid climate change.